Mengurai Polemik TikTok Shop di Indonesia: Analisis Jaringan Tweet Bertagar #KamiUMKMdiTikTok - Dahana, Abyzan Syahadin Bagja; Widagdhaprasana, Massageng (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
Previous research has shown that hashtags on social media become a collective means for people to counter the discourse echoed by other groups. This study expands on previous research by taking the case of tweets with the tag #KamiUMKMdiTikTok trending on X. This study aimed to describe the dynamics of conversation in X related to tweets with the tag #KamiUMKMdiTikTok. This study applied social network analysis (SNA) to 1,403 Indonesian tweets and their amplification (retweets) published from September 25 to October 10, 2023. The results of SNA with the Gephi application show that communication networks have tenuous characteristics because the delivery of opinions in the form of tweets is spread across many conversation clusters, so the dominant actor does not control the continuity of the conversation in general. Therefore, the emergence of tweets with the tag #KamiUMKMdiTikTok is relatively short-lived and reflects the practice of the digital movement of opinion. The study also applied qualitative content analysis to identify narrative framing strategies in tweets. Analysis shows that the hashtag #KamiUMKMdiTikTok reflects the disappointment and criticism of merchants at TikTok Shop against the government's insistence that TikTok Shop stop its operations in Indonesia.